Catalytic Electrophilic C−H Borylation Using NHC⋅Boranes and Iodine Forms C2‐, not C3‐, Borylated Indoles. Issue 34 (31st May 2017) - McGough, John S.; Cid, Jessica; Ingleson, Michael J.
Abstract: Activation of N‐heterocyclic carbene boranes (NHC⋅BH3 ) by I2 enables the metal‐free catalytic C−H borylation of heteroarenes with formation of H2 as the by‐product in a process that uses only bench stable precursors. The borylation of indoles using NHC⋅BH3 /I2 produces C2‐borylated indoles exclusively in contrast to other catalytic electrophilic C−H borylation methods. Mechanistic studies indicate that this is due to C3 to C2 boron migration facilitated by the absence of exogenous Brønsted bases. Thus this C−H borylation methodology proceeds under sufficiently Brønsted acidic conditions to enable the thermodynamic C2‐borylated indole isomer to be formed instead of the C3 borylated‐isomer. This demonstrates that electrophilic C−H borylation can be used to access a wider range of borylated regioisomers than reported to date. Abstract : I′ll C2 it ! Activation of N‐heterocyclic carbene boranes by I2 enables the metal‐free catalytic C−H borylation of heteroarenes with formation of H2 as the by‐product in a process that requires only bench stable precursors. The C−H borylation of indoles using NHC⋅BH3 /I2 produces C2‐borylated indoles exclusively in contrast to other catalytic electrophilic C−H borylation methods.